The Effectiveness Of The Use Of Professional Competence And The Use Of Targeted Video Materials In The Training Of Management Personnel - Maxkamov Navruzjon Tukhtamishevich (International Journal on Economics, Finance and Sustainable Development, 2021)
The article describes the rules and results of the use of video materials for specific purposes aimed at improving the skills of management, in particular, the development of management skills. That is why it is very important to use video materials with clear goals in improving the skills of management staff, the development of management skills, and through this we can achieve clear positive results. For this research, assignments were given to 2 groups of 40 students of the Samarkand regional branch of the Academy of Public Administration under the President of the Republic of Uzbekistan, each with 20 participants, and after the training tests were conducted. According to the results of the training, which was organized with general information, without taking into account the specifics of the group, the indicator of mastering the topic of group 1 was 12 points. According to the results of the training, which was organized by selecting video materials on the topic, taking into account the area of ​​activity of the group members, the field, and other factors, the mastery of the topic in group 2 was 18 points. The article reveals the importance of competent teachers in the in-service training system. Because if the teacher has professional competencies, the training will be effective if the lessons are organized in a way that is as understandable to the listener as possible using interactive methods